Romantic Gothic : an Edinburgh companion - Wright, Angela, 1969 May 14-; Townshend, Dale (Edinburgh companions to the Gothic, 2015)
Romantic Gothic: An Edinburgh Companionoffers a rigorous account of the Gothic impulses informing British, American and European literary culture of the late eighteenth and early nineteenth centuries.